PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM MELALUI PROFITABILITAS SUBSEKTOR TELEKOMUNIKASI - Nely Tangke Rante (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to examine the effects of liquidity, proxied by the Quick Ratio (QR) and Current Ratio (CR), and solvency, proxied by the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), on stock prices through profitability as a mediating variable, which is proxied by the Return on Assets (ROA) and Return on Equity (ROE). The data used in this research are secondary data obtained from annual reports. The sample consists of 9 telecommunications subsector companies listed on the Indonesia Stock Exchange that meet the sampling criteria, covering the period from 2019 to 2023 (5 years), resulting in 45 observed data points. This study employs SmartPLS 4 as the analytical tool using a quantitative method. The findings indicate that liquidity has a positive and significant effect on profitability. Solvency has no effect on profitability or stock prices. Liquidity has no effect on stock prices. Profitability also has no effect on stock prices. Furthermore, liquidity and solvency do not affect stock prices through profitability as a mediating variable.